IDENTITAS DAN POSISI PEREMPUAN DALAM ROMAN L’ENFANT DE SABLE KARYA TAHAR BEN JELLOUN - Sunahrowi, nfn; Damayanti, Gandis Prastiwi (SUAR BETANG, 2017)
Identity and gender are sensitive issues in the third world. This issue has always clashed with the cultural nature of human beings and also become a foreign territory for them. Both men and women become opposite positions. They occupy different places in third world society. Women are culturally stereotyped less favourable for existence in the presence of men. Tahar Ben Jelloun, a French-born Moroccan author, was able to take quite a careful situation in his neighbourhood. He, in the novel L'Enfant de Sable is able to provide a clear picture of the position and identity of Algerian women and at the same time also posing with male characters. He who was born of a third world society was able to draw these themes into postcolonial issues, primarily on the themes of women and their existence in society.